"I'm Never Coming Back from that Trip": The 1994 ANU Occupation and Student Protest Beyond the 1960s. Issue 2 (3rd April 2019) - Briedis, Tim
ABSTRACT: In 1994 a major student occupation took place at the Australian National University (ANU) in Canberra in response to plans to introduce upfront fees. Coming twenty years after a similar 1974 occupation at ANU, the past was weaponised both by critics of the occupations and activists themselves. Critics argued that the 1990s protestors were solely motivated by self-interest and that their activism was far inferior to the radicalism of the Long Sixties. Simultaneously, activists invited veterans of the 1974 occupation to speak to the protestors and tried to treat the past pedagogically. Drawing on extensive oral history, this article analyses the 1994 occupations. It argues that the occupations have helped to complicate a historiographic narrative of the student movement's decline and moderation since the 1960s. Interviews show the thought, creativity and emotion invested in the occupations and their long-term effect on people's lives. Unlike 1974, activists resisted management attempts to funnel protest into bureaucracy. Above all, the occupation provided a glimpse into an alternative world, where student radicals "lived and breathed the occupation" and where "full on fucking direct democracy" could function, even if only momentarily.